Evaluating the effect of in-situ rainwater harvesting techniques on maize production in moisture stress areas of humbo woreda, wolaita zone, southern Ethiopia - Naba, W; Moges, A; Gebremichael, A (International Journal of Agricultural Research, Innovation and Technology, 2020)
The study was conducted to investigate the effect of different in-situ water harvesting structures as soil moisture conservation techniques under maize crop production in Abela Sippa kebele Wolaita zone, Ethiopia where rainfall variation is affecting agriculture with prolonged dry spells during critical crop growth stages. The experiment was laid out in a Randomized Complete Block Design, with three replications and four treatments. The four treatments used in the study were; Control, Targa, Tie-ridge and Zai pits. Findings from this study revealed that maize grain yield and yield components, such as, grain yield, dry matter biomass, and cob length were highly significant (p<0.05) on Targa. Soil-moisture content over the crop growing season at dry spell periods was significantly higher in Targa and Tie ridges than the control. Maize yield of (7150 kg ha-1), (6190 kg ha-1), (4500 kg ha-1) and (4900 kg ha-1) was obtained from Targa, Tie ridge, Zai pits and Control, respectively. Targa and Tie ridge treatments recorded higher net returns (29712 and 25164 kg ha-1) than Control (20370 kg ha-1) and Zai (14350 kg ha-1) treatments. The results revealed that the in-situ rainwater harvesting techniques could play great role in improving crop yield in dry periods. However, the utilization of the technology is surrounded by various constraints. The major constraints include labour, cost, lack of knowledge and crops planted on bunds. The findings suggest that Targa structure improved water availability during the growing season, thereby protecting crops from dry periods and it needs minimum cost, less labor power ,and easily constructed by local farmers (not require complicated knowledge). Int. J. Agril. Res. Innov. Tech. 10(1): 71-79, June 2020